Hadith #4293 - Sunan Abi Dawud - Abdullah bin Qays, Abu Bahriyya عبد الله بن قيس الكندي أبو بحرية; Abu Bakr bin 'Abdullah bin Abi Maryum أبو بكر بن عبد الله بن أبي مريم; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; al-Walid bin Sufyan bin Aby الوليد بن سفيان بن أبي مريم الغساني; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Mu'adh ibn Jabal (Sunan Abi Dawud)
The Muslims will then make for their weapons and will fight, and Allah will honor that body with martryrdom. Abu Dawud said: But al-Walid has narrated this tradition from Dhu Mikhbar from the Prophet (ﷺ). Abu Dawud said: Rawh, Yahya bin Hamzah and Bishr bin Bakr has also transmitted it from al-Awza’i as mentioned by ‘Isa.
Grade: Sahih

Hadith #5128 - Sunan Abi Dawud - Abu al-Darda; Abu Bakr bin 'Abdullah bin Abi Maryum أبو بكر بن عبد الله بن أبي مريم; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Bilal bin Abi al-Drda'a بلال بن أبي الدرداء الأنصاري; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Khalid bin Muhammad al-Thqfy خالد بن محمد الثقفي الدمشقي (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who is consulted is trustworthy.
Grade: Sahih

Hadith #1010 - Jami' al-Tirmidhi - Abu Bakr bin 'Abdullah bin Abi Maryum أبو بكر بن عبد الله بن أبي مريم; Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Rashid bin Sa'd راشد بن سعد; Thawban bin Bujdud (Jami' al-Tirmidhi)
“The Messenger of Allah would walk in front of the funeral, as did Abu Bakr, Umar and Uthman.”
Grade:

Hadith #2576 - Jami' al-Tirmidhi - Abdullah bin 'Abdur Rahman al-Daarimi عبد الله بن عبد الرحمن الدارمي; Abdullah bin Mubarak عبد الله بن المبارك; Abu Bakr bin 'Abdullah bin Abi Maryum أبو بكر بن عبد الله بن أبي مريم; Amr bin 'Awn/'Auf bin Aws; Damrah bin Habib al-Zubaidi ضمرة بن حبيب بن صهيب الزبيدي; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Shadad bin Aus bin Thabit; Sufyan bin Wky' bin al-Jrah سفيان بن وكيع بن الجراح (Jami' al-Tirmidhi)
“Indeed a disbeliever’s skin will be forty-two forearm lengths thick, his molar teeth will be like Uhud (mountain), and his sitting place in Hell will be like what is between Makkah and Al-Madinah.”
Grade:

Hadith #1547 - Sunan Ibn Majah - Abu Bakr bin 'Abdullah bin Abi Maryum أبو بكر بن عبد الله بن أبي مريم; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Kathir bin 'Ubaid bin Nmyr كثير بن عبيد بن نمير المذحجي; Rashid bin Sa'd راشد بن سعد (Sunan Ibn Majah)
the Messenger of Allah said: “I have exempted you from having to pay Sadaqah on horses and slaves.”
Grade:

Hadith #4227 - Sunan Ibn Majah - Abdullah bin Qays, Abu Bahriyya عبد الله بن قيس الكندي أبو بحرية; Abu Bakr bin 'Abdullah bin Abi Maryum أبو بكر بن عبد الله بن أبي مريم; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; al-Walid bin Sufyan bin Aby الوليد بن سفيان بن أبي مريم الغساني; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Mu'adh ibn Jabal; Yazid bin Qtyb يزيد بن قطيب (Sunan Ibn Majah)
A poet praised Bilal bin ‘Abdullah and said: “Bilal bin ‘Abdullah is better than any other Bilal.” Ibn ‘Umar said: ‘You are lying. The Bilal of the Messenger of Allah is better than any other Bilal.'”
Grade: